2018
DOI: 10.1093/jas/sky188
|View full text |Cite
|
Sign up to set email alerts
|

Hens ranked as highly feed efficient have an improved albumen quality profile and increased polyunsaturated fatty acids in the yolk1

Abstract: The shelf life of eggs that contain elevated levels of polyunsaturated fatty acids (PUFA) is compromised due to the relative instability and therefore greater potential for lipid peroxidation of unsaturated fatty acids (FA). Poultry that is highly feed efficiency (HFE) exhibits higher systemic levels of antioxidant enzymes and therefore may produce eggs with improved albumen quality and favorable FA profiles that are stable over time. We tested the hypothesis that HFE-laying hens produce eggs with improved int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Laying performance and egg quality are profoundly affected by the metabolic status of laying hens. It has been proven that physiological stress, including metabolic rate, energy consumption, and catabolism, directly affects egg quality (Kim and Choi, 2014;Akter et al, 2018). In this study, increases in serum LH and FSH levels were associated with an improvement in the productive performance of laying hens.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Laying performance and egg quality are profoundly affected by the metabolic status of laying hens. It has been proven that physiological stress, including metabolic rate, energy consumption, and catabolism, directly affects egg quality (Kim and Choi, 2014;Akter et al, 2018). In this study, increases in serum LH and FSH levels were associated with an improvement in the productive performance of laying hens.…”
Section: Discussionmentioning
confidence: 65%
“…It has been reported that higher contents of MUFA and PUFA, as well as a lower content of SFA, as found in the egg yolks from GML-treated groups, could contribute to a decrease in the negative influences of high cholesterol levels in eggs (Milinsk et al, 2003). Fatty acids, which are deposited in yolks, are synthesized from excess carbohydrates and amino acids in hens' livers (Akter et al, 2018). The enrichment of fatty acids in the yolk by GML treatment might be attributed to the reduction of FCR, which could increase the absorption of carbohydrates and protein from feed in laying hens (Jin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between FCR and BW change in the present study is consistent with a study by Lacin et al [ 4 ], who reported positive associations between BW and FCR. Similarly, Akter et al [ 11 ] reported that hens classed as highly feed efficient, with an FCR value of <1.8, had a significantly lighter BW when compared to hens ranked as poorly feed efficient, FCR > 2.1.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study, it was observed that hens ranked as having a high FCR had greater BW and produced eggs with a lower Haugh unit [ 11 ]. In the present study, the absence of an association between feed intake and albumen height, BW indices and albumen height and albumen weight suggests that neither increased feed consumption nor increased hen body weight was associated with albumen quality in early-laying hens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation